Sex Differences in Autonomic Cardiac Control and Oxygen Saturation Response to Short-Term Normobaric Hypoxia and Following Recovery: Effect of Aerobic Fitness - Botek, Michal; Krejčí, Jakub; McKune, Andrew (Frontiers in Endocrinology, 2018)
Introduction: The main aims of this study were to investigate autonomic nervous system (ANS) and arterial oxygen saturation (SpO2) responses to simulated altitude in males and females, and to determine the association between maximal oxygen uptake (VO2max) and these responses. Materials and Methods: Heart rate variability (HRV) and SpO2 were monitored in a resting supine position during Preliminary (6 min normoxia), Hypoxia (10 min, fraction of inspired oxygen (FiO2) of 9.6%, simulated altitude 6,200 m) and Recovery (6 min normoxia) phases in 28 males (age 23.7 ± 1.7 years, normoxic VO2max 59.0 ± 7.8 ml.kg−1.min−1, body mass index (BMI) 24.2 ± 2.1 kg.m−2) and 30 females (age 23.8 ± 1.8 years, VO2max 45.1 ± 8.7 ml.kg−1.min−1, BMI 21.8 ± 3.0 kg.m−2). Spectral analysis of HRV quantified the ANS activity by means of low frequency (LF, 0.05–0.15 Hz) and high frequency (HF, 0.15–0.50 Hz) power, transformed by natural logarithm (Ln). Time domain analysis incorporated the square root of the mean of the squares of the successive differences (rMSSD). Results: There were no significant differences in SpO2 level during hypoxia between the males (71.9 ± 7.5%) and females (70.8 ± 7.1%). Vagally-related HRV variables (Ln HF and Ln rMSSD) exhibited no significant differences between sexes across each phase. However, while the sexes demonstrated similar Ln LF/HF values during the Preliminary phase, the males (0.5 ± 1.3) had a relatively higher (p = 0.001) sympathetic activity compared to females (−0.6 ± 1.4) during the Hypoxia phase. Oxygen desaturation during resting hypoxia was significantly correlated with VO2max in males (r = −0.45, p = 0.017) but not in females (r = 0.01, p = 0.952) and difference between regression lines were significant (p = 0.024). Conclusions: Despite similar oxygen desaturation levels, males exhibited a relatively higher sympathetic responses to hypoxia exposure compared with females. In addition, the SpO2 response to resting hypoxia exposure was related to maximal aerobic capacity in males but not females.